Renewable energy strategies for alleviating energy poverty in informal settlements : a case study of Diepsloot-South Africa - Nsubuga, F.W.N. (Francis Wasswa Nkugwa) (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2020.